Pembentukan Humanisme Religus dalam Multikultural Agama di Desa Kemanukan Kecamatan Bagelen Kabupaten Purworejo - Yazid Al Ansori (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Radicalism, especially in a multicultural society, not only threatens the integrity of the state, but also affects the stability of religious life among adherents of the religion itself, especially among those with different religions. Kemanukan Village apparatus, religious leaders, community leaders, and traditional leaders in the village. They stated that in Kemanukan Village, Bagelen District, Purworejo Regency, there are religious differences, as well as cultural differences. This study aims to determine the concept of da'wah in realizing religious humanism in multicultural religions. This study is intended to answer the problem of how the concept of religious humanist-based Islamic da'wah in Kemanukan Village, Bagelen District, Purworejo Regency and the relevance of religious humanists in the context of today's Islamic Da'wah. These problems were discussed through field studies where data were obtained from various interviews related to religious humanists and direct interviews. All research data were analyzed using descriptive analysis method. The results of this study indicate that: (1) Religious humanism is a religious perspective that places humans as humans and an effort to humanize the sciences with full faith accompanied by human relationships with Allah SWT and fellow humans or hablun min Allah and hablun min al- text. Implementation in Islamic da'wah emphasizes the aspects of common sense, individualism towards independence, the spirit of seeking knowledge, Islamic da'wah in pluralism, emphasizing functions rather than symbols, and a balance between reward and punishment. (2) In the context of today's Islamic da'wah, Islamic da'wah must be oriented towards non-dichotomous education. By not separating the two dimensions of science, namely religious science and general science.